Mengenal Kesulitan Tenaga Pendidik dalam Manajemen Kelas di sekolah MIS Seroja Dua Sei Rotan - Cahaya Mustika; Chairunnisa Nasution; Irma Liani; Elya Siksa Anggraini (Universitas Palangka Raya, 2024)
Efforts to improve the quality of learning in schools are a form of challenge that educators must have experienced. One of the main factors that has quite an influence on the quality of learning is the strategy in carrying out classroom management which is still felt to be ineffective. This research aims to identify the difficulties of teaching staff or teachers in classroom management at MIS SEROJA DUA SEI ROTAN. The research method used in this study is a descriptive qualitative research approach. The problem of difficulties in managing classroom management will be an area of ​​our work to be able to dig up information regarding problem analysis and also provide appropriate solutions to the root of the problem. The research results show that implementing effective classroom management strategies helps provide a positive impact on learning. This research offers important implications for teachers, school principals, and educational policy makers. Teachers need to receive training and assistance in implementing effective classroom management strategies.